Governance of flagship events in Surakarta City case studies of Solo International Performing Arts (SIPA), Solo Batik Carnival (SBC), and Solo Keroncong Festival (SKF) - Kusumorasri, Irawati; Prihatini, Nanik Sri; Sunarto, Bambang (Gelar: Jurnal Seni Budaya, 2023)
The implementation of cultural events or festivals is part of efforts to revitalize the tourism sector in Surakarta City. The cultural event has succeeded in becoming a means of tourism development. The possibilities are present and have given birth to a performance program. The most significant event activities include Solo International Performing Arts (SIPA), Solo Batik  Carnival (SBC), and Solo Keroncong Festival (SKF). This research aims to know the governance principles for organizing a good festival or cultural event. Hopefully, understanding the principles of governance to make SIPA, SBC, and SKF become the flagship event in Surakarta city will serve as managerial knowledge useful in developing festivals and cultural events. It is important to study the management of SIPA, SBC, and SKF to find out the characteristics of leading event management so that they are included in the leading criteria. Research produces theoretical solutions, so that festival management has an adaptive and applicable management system for organizing events. The findings will be useful as a reference for other cultural events in the city of Solo. The research uses explanatory methods to find and create concepts that clarify SIPA, SBC, and SKF into three flagship events. Implementing this event is successful because it uses the combined governance between modern management and traditional management. For this reason, the results of this study have significant meaning because they can at least serve as a model in the organization of festivals and cultural events in other places